2009
DOI: 10.1007/s10499-009-9250-x
|View full text |Cite
|
Sign up to set email alerts
|

Stocking density for the intensive rearing of juvenile crayfish, Pacifastacus leniusculus (Astacidae), using Artemia nauplii to supplement a dry diet from the onset of exogenous feeding

Abstract: Recent advances in intensive rearing of astacid juvenile crayfish have greatly improved the results. This challenges the current application possibilities of the studies performed previously, and new research on density is required. A 100-day experiment was carried out under controlled conditions to evaluate density effects on survival and growth rates of juvenile crayfish in optimal conditions of feeding. Juvenile stage 2 Pacifastacus leniusculus were stocked in fibreglass tanks (1 m 2 , 200 l water) at 20 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
1
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 15 publications
2
34
1
4
Order By: Relevance
“…The proportion of crayfish with non-injured chelae (54.5%) was higher than that reported by González et al (2010) who found a 41.5% incidence of chelae injury in 391 surviving juveniles from an initial density 1000 crayfish·m −2 after a 100-day experiment. This may reflect decreasing frequency of chela injuries over time (see González et al, 2010) suggesting cannibalization of injured animals by intact ones together with regeneration of damaged appendages (Mason, 1979;Buȓic et al, 2009).…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…The proportion of crayfish with non-injured chelae (54.5%) was higher than that reported by González et al (2010) who found a 41.5% incidence of chelae injury in 391 surviving juveniles from an initial density 1000 crayfish·m −2 after a 100-day experiment. This may reflect decreasing frequency of chela injuries over time (see González et al, 2010) suggesting cannibalization of injured animals by intact ones together with regeneration of damaged appendages (Mason, 1979;Buȓic et al, 2009).…”
Section: Discussioncontrasting
confidence: 63%
“…This may reflect decreasing frequency of chela injuries over time (see González et al, 2010) suggesting cannibalization of injured animals by intact ones together with regeneration of damaged appendages (Mason, 1979;Buȓic et al, 2009). Higher levels of injury to chelae, which are relatively robust, along with lesser damage to the more fragile walking legs (Table II), suggests that cannibalism must occur relatively quickly, especially in cases of bilateral chela damage.…”
Section: Discussionmentioning
confidence: 99%
“…With this in mind, future research on nutrition of juvenile astacids through specific practical diets should also include fat content adjustment. Regarding the stocking density for the intensive rearing of juvenile astacids, the best results have been obtained with 100 crayfish·m −2 (Savolainen et al, 2004;González et al, 2010) or less (Ackefors et al, 1989;Nyström, 1994), whereas higher densities resulted in higher biomass but reduced survival and growth rates. In the present study, the feeding conditions allowed an increase from 100 to 200 crayfish·m −2 with no reduction in survival or growth, biomass values being doubled.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the poor results obtained on freshwater crayfish, the limited supply and high price of this diet discouraged its further use on crayfish research. A wide variety of natural foods (mainly fresh or frozen animals and vegetables) and feedstuffs formulated for other aquatic species either alone or supplemented with natural foods (see review by González R. et al, 2009a) have been tested to improve survival and growth rates of astacid juveniles from the onset of exogenous feeding. However, acceptable results have been only obtained by supplying live feed such as Daphnia or Artemia nauplii (Sáez-Royuela et al, 2007;González À. et al, 2008González À. et al, , 2011González R. et al, 2009a).…”
Section: Introductionmentioning
confidence: 99%
“…A wide variety of natural foods (mainly fresh or frozen animals and vegetables) and feedstuffs formulated for other aquatic species either alone or supplemented with natural foods (see review by González R. et al, 2009a) have been tested to improve survival and growth rates of astacid juveniles from the onset of exogenous feeding. However, acceptable results have been only obtained by supplying live feed such as Daphnia or Artemia nauplii (Sáez-Royuela et al, 2007;González À. et al, 2008González À. et al, , 2011González R. et al, 2009a). Recently, González R. et al (2009b) proved that decapsulated Artemia cysts can be better supplement than live nauplii, since cysts improve the performance of juvenile crayfish, allowing a reduction of labour and costs.…”
Section: Introductionmentioning
confidence: 99%